Die urheberrechtliche Zwangslizenz - Weber, Hubertus (Abhandlungen zum Urheber- und Kommunikationsrecht, 2018)
Copyright law prevents market failure by making intangible goods exclusive and thus marketable. Exclusivity, however, has a downside: If the right holder prohibits uses without making them himself (in a certain way), out-of-print works lie dormant, innovations are hindered, and scientific journals are made prohibitively more expensive. The remedy could be a compulsory copyright licence. This special type of obligation to contract regulated by copyright law - the right holder must grant a licence, but can negotiate the conditions - leads a shadowy existence in literature and legislation. The aim of the work is to close this gap. First, using a comparative law approach and the goal of "normative efficiency", the author analyses whether and in which cases a compulsory copyright licence should be regulated. He then examines how the compulsory copyright licence could be designed in order to be effective and compatible with international, EU and constitutional law.